PRIORITIZING FLOOD MITIGATION IN VILLAGES AFFECTED BY THE PALASARI DAM BREAK USING TOPSIS - Ni Luh Putri Prabandari; I Putu Gustave Suryantara Pariartha; Silvia Gabrina Tonyes (Journal of Infrastructure Planning and Engineering, 2025)
Dam collapse is a disaster that has the potential to have a significant impact on communities in downstream areas. This study aims to determine priorities for handling villages affected by flooding due to the collapse of the Palasari Dam in Jembrana Regency, Bali, using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The data used was obtained from the results of hazard classification analysis based on InaSAFE software which includes four main parameters, namely the area of inundation, length of affected roads, number of affected buildings and number of affected populations. Each parameter is grouped by village and given a weight based on the principle of disaster vulnerability by placing life safety as the main priority. The results of the analysis show that the villages of Nusasari, Candikusuma, and Tuwed are the villages with the highest treatment priority, each with a preference value of 0.760; 0.605; and 0.524. The TOPSIS method has proven effective in combining spatially based quantitative data to support objective and systematic disaster mitigation decision making. This research also provides a basis for preparing a more adaptive Emergency Action Plan (EAP).